TikTok dan Kesehatan Mental: Studi Pengaruh Media Sosial pada Remaja - Carolan, Farrin; Lawwin, Jay; Jovin, Jovin; Ronald, Ronald; Novisari, Winny (Forum Kerjasama Pendidikan Tinggi (FKPT), 2025)
This study aims to analyze how the use of TikTok affects the mental health of adolescents in Batam. The method used in this study is a quantitative method using a survey, involving 405 participants aged between 10 and 24 years who actively use TikTok. Based on data from 405 respondents, 86.9% (352 respondents) actively use TikTok, covering all levels of adolescent education. The data collection tool was a questionnaire with a Likert scale designed to measure independent variables (TikTok use) and dependent variables (mental health, including depression, anxiety, stress, and bipolar disorder). Data analysis was performed using the Structural Equation Modeling (SEM) method with AMOS software. The results of this study indicate that TikTok usage significantly contributes to an increase in symptoms of depression, anxiety, stress, and bipolar disorder among adolescents. The reliability test results show that the Cronbach's Alpha values for the variables TikTok Usage (TU) are 0.768, Depression (D) are 0.801, Stress (S) are 0.872, Anxiety (A) are 0.868, and Bipolar Disorder (BD) are 0.874. Based on standard interpretation, a Cronbach's Alpha value greater than 0.70 is considered to have adequate reliability. Therefore, all variables indicate that the items in the questionnaire have a good level of internal consistency. These findings highlight the importance of improving digital literacy and time management in social media use to maintain adolescent mental health. This study provides valuable insights into understanding the complex relationship between social media and mental health, as well as providing a foundation for more effective interventions in the future.